PENGARUH INFLASI, FINANCING TO DEPOSIT RATIO (FDR), RATIO FINANCING (RF) DAN RATIO RETURN (RR) TERHADAP NON PERFORMING FINANCING (NPF) PADA PT.BANK BRI SYARIAH PERIODE TAHUN 2009 SAMPAI 2015 - Iyan, Rita Yani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
(FDR), Ratio Financing (RF) and Ratio Return (RR) to Non Performing Financing (NPF) on PT.Bank BRI Syariah. This research using descriptive analysis and quantitative analysis, partial and simultaneous analysis (multiple linear regression analysis using SPSS VERSION 20 program facility). The results of tests that have been conducted, simultaneous regression test (Test F) shows that inflation, Financing to Deposit Ratio (FDR), Ratio Financing (RF) and Ratio Return (RR) together influential and significant to Non Performing Financing (NPF) on PT.Bank BRI Syariah. Regression test (t Test) showed that inflation variable has a positive and significant impact to NPF on PT.Bank BRI Syariah, FDR variable has a positive and significant to NPF on PT.Bank BRI Syariah, RF variable has a positive and significant to NPF on PT.Bank BRI Syariah and RR variable has a positive and significant to NPF on PT.Bank BRI Syariah. The influence of the NPF PT.Bank BRI Syariah explained by the variable inflation, Financing to Deposit Ratio (FDR), Ratio Financing (RF) and Ratio Return (RR) together amounted to 68,9% (